RASTRIYA SWASTHYA BIMA YOJANA AND HEALTH EQUITY: USER EXPERIENCES AND REFLECTIONS FROM ODISHA. (7th July 2016) - Patel, Gupteswar; Patel, Kripalini
Abstract : Background: The India, the below-poverty-line population (BPL) accounts for approximately 357.6 million people. Rastriya Swasthya Bima Yojana (RSBY) is a public-private health insurance scheme for BPL families implemented by the government of India in 2008, which seeks to improve access to quality health services while reducing out-of-pocket expenditure. The RSBY provides insurance coverage up to INR 30, 000 for maximum five family members, to be utilised at public or empanelled private hospitals. A range of studies has identified barriers associated with RSBY, including limited financial coverage, low enrolment, and low public awareness. The perspective of the end-users however remains largely under-explored. We explored the experiences of beneficiaries who used the RSBY during hospitalisation. Methods: Our qualitative in-depth study was conducted in 2013 in a coastal district of Odisha. We interviewed 18 RSBY beneficiary families to elicit their out-of-pocket expenditure (OOP), utilisation of RSBY during hospital stay, and experiences and reflections on hospitalisation. Respondents were purposefully selected from the pool of patients who had used RSBY in public or private hospitals in the past one month at the time of data collection, for a hospital stay of no less than two days. After obtaining informed consent, semi-structured in-depth interviews were conducted with patients and their family members. Interviews were audio recorded and transcribed into English. Content analysis enabled the identification and categorisation of themes, and their detailed exploration. Findings: Out of 18 respondents, 11 had visited public and private hospitals, four had visited private hospitals, and three had visited public hospitals. Beneficiaries stated that public hospitals remain under-equipped in comparison to the private ones. Regarding financial protection provided by RSBY, respondents were pleased to have been able to access costly medicines at but private and public hospital without spending out-of-pocket. In private hospitals however, beneficiaries had to spend extra money on travel to bring hard copies of supportive documents such as ID proof. Also in private hospitals, some respondents still incurred high OOP payment when the INR 30, 000 RSBY coverage was exhausted. They also described feeling ashamed in case they could not afford to continue treatment. Respondents felt neglected and discriminated at private hospitals while utilising in-patient services. Many experienced rude behaviour of hospital staff, which they attributed to the fact that they were RSBY beneficiaries. They felt RSBY creates a boundary between poor and rich people within private hospitals. According to some respondents, many private hospitals refuse to admit RSBY cardholders to their in-patient department. Respondents often had become reluctant to visit private hospitals where, as RSBY patients, they had negative previous experiences. Discussion: Our study reflects that although RSBY helped some beneficiaries to afford medicines and in-patient services at private and public hospitals, health inequities remain a major issue, particularly so in private hospitals. When accessing services, RSBY cardholders continued to face economic and social barriers to quality care, including out-of-pocket expenditure, discrimination, and denial of care. To realise the equity objectives of RSBY, empanelled hospitals must be well regulated, which is not part of the RSBY design and not the case today. Other studies have highlighted a range of issues with RSBY and its implementation, such as low awareness and enrolment, lack of transparency and monitoring of private insurers and hospitals, and financial barriers. This study adds discrimination while utilising health care as another major implementation issue with RSBY. Empanelled hospitals should respect the 'cashless' nature of RSBY, but also adhere to non-discriminatory practices while delivering services. Conclusion: Financial barriers and discrimination are common experiences of RSBY users in Odisha, deterring the scheme from its equity objective and the potential beneficiaries from future care seeking. Through effective regulation, the RSBY state nodal agency should optimise financial protection and redress discrimination in service utilisation. No competing interest .